Long-term assessment of wild boar harvesting and cattle removal for bovine tuberculosis control in free ranging populations. - Gregorio Mentaberre (Public Library of Science (PLoS), 2014)
Wild boar is a recognized reservoir of bovine tuberculosis (TB) in the Mediterranean ecosystems, but information is scarce outside of hotspots in southern Spain. We describe the first high-prevalence focus of TB in a non-managed wild boar population in northern Spain and the result of eight years of TB management. Measures implemented for disease control included the control of the local wild boar population through culling and stamping out of a sympatric infected cattle herd. Post-mortem inspection for detection of tuberculosis-like lesions as well as cultures from selected head and cervical lymph nodes was done in 745 wild boar, 355 Iberian ibexes and five cattle between 2004 and 2012. The seasonal prevalence of TB reached 70% amongst adult wild boar and ten different spoligotypes and 13 MIRU-VNTR profiles were detected, although more than half of the isolates were included in the same clonal complex. Only 11% of infected boars had generalized lesions. None of the ibexes were affected, supporting their irrelevance in the epidemiology of TB. An infected cattle herd grazed the zone where 168 of the 197 infected boars were harvested. Cattle removal and wild boar culling together contributed to a decrease in TB prevalence. The need for holistic, sustained over time, intensive and adapted TB control strategies taking into account the multi-host nature of the disease is highlighted. The potential risk for tuberculosis emergence in wildlife scenarios where the risk is assumed to be low should be addressed.